2015
DOI: 10.1002/ldr.2393
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Functions After Forest Fires Affected by the Compost Quality

Abstract: Composts are frequently used to restore various degraded lands especially after fire. We investigated how different organic amendments after frequent wildfires can affect soil microbial functions. We crossed three times since fire (1, 5 and 18 years) with three different compost qualities (i.e. young, intermediate and old). After 5 months, alkaline phosphatase increased by the intermediate compost in early post-fire chronosequence (1 and 5 year after fires). This increase was confirmed 10 months after amendmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Descriptive statistics and Student t-test mean difference analysis of the area of interest and the reference area for organic matter (OM, %), available phosphorus (P, ppm), pH, aluminum (Al, meq/100 g soil), and the exchangeable bases calcium (Ca), magnesium (Mg), potassium (K), and sodium (Na) meq/100 g soil. The use of wastewater can improve the nutritional content of agricultural soils, which is why wastewaters are used in many countries as an alternative to organic manures, generating a decrease in production costs [29,59]. The highest phosphorus contents were found in the area where recent agricultural activities had been conducted, while low phosphorus content existed on land that had not been in agricultural use over the past year (Figure 3).…”
Section: Chemical Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Descriptive statistics and Student t-test mean difference analysis of the area of interest and the reference area for organic matter (OM, %), available phosphorus (P, ppm), pH, aluminum (Al, meq/100 g soil), and the exchangeable bases calcium (Ca), magnesium (Mg), potassium (K), and sodium (Na) meq/100 g soil. The use of wastewater can improve the nutritional content of agricultural soils, which is why wastewaters are used in many countries as an alternative to organic manures, generating a decrease in production costs [29,59]. The highest phosphorus contents were found in the area where recent agricultural activities had been conducted, while low phosphorus content existed on land that had not been in agricultural use over the past year (Figure 3).…”
Section: Chemical Analysismentioning
confidence: 97%
“…Wastewater may contain residues of industrial or domestic origin as well as urban runoff [16,28]. Guénon et al [29] reported that, in untreated wastewater, concentrations of Pb and methylmercury can reach 0.16 ± 0.05 mg/L and 3.8 ± 2.5 ng/L, respectively. Recently, technologies such as biochar have been proposed to phytostabilize contaminants in the soil and could potentially sequester contaminates and convert soils degraded by contamination into productive ecosystems once again [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The potential use of compost to restore nutrient cycling of fire‐affected areas is studied by Guénon & Gros (, this issue). Microbial activity involved in the main nutrient cycles was evaluated after the addition of composts of different qualities to a chronosequence of fire‐affected Mediterranean areas.…”
Section: Additional Insightsmentioning
confidence: 99%
“…It is widely accepted that studying soil requires an interdisciplinary view and soil should not be understood like a single science (Brevik et al ., ), especially after perturbations like fires. Changes in soil properties after a fire have direct and indirect consequences on water resources (Keesstra et al ., ), vegetation and microorganisms (Guénon et al ., ; Guénon & Gross, ; Wang et al ., ) between others. Many of the soil services, which are essential to humans and environment, are provided by soil biota.…”
Section: Introductionmentioning
confidence: 98%